Effect of Regular Training on Platelet Function in Untrained Thoroughbreds - Arianna Miglio; Emanuela Falcinelli; Katia Cappelli; Samanta Mecocci; Anna Maria Mezzasoma; Maria Teresa Antognoni; Paolo Gresele (Animals, 2024)
Training has a significant effect on the physiology of blood coagulation in humans and in horses. Several hemostatic changes have been reported after exercise in the horse but data available are inconclusive. The aim of this study was to investigate platelet activation and primary platelet-related hemostasis modifications in young never-trained Thoroughbreds in the first incremental training period in order to improve knowledge on this topic. Twenty-nine clinically healthy, untrained, 2-year-old Thoroughbred racehorses were followed during their incremental 4-month sprint exercise training. Blood collection was performed once a month, five times in total (T-30, T0, T30, T60, and T90). Platelet aggregation was measured by light transmission aggregometry in response to various agonists: adenosine diphosphate (ADP), collagen, and calcium ionophore A23187. Platelet function was evaluated using a platelet function analyzer (PFA-100®) using collagen/ADP and collagen/adrenaline cartridges. Nitrite-nitrate (NOx) plasma concentrations were measured via a colorimetric assay to assess in vivo nitric oxide bioavailability. Platelet activation was also investigated through gene expression analyses (selectin P-SELP, ectonucleotidase CD39-ENTPD1, prostaglandin I2 synthase-PTGIS, endothelial nitric oxide synthase 3-NOS3). Differences among the time points were analyzed and mean ± SEM were calculated. Significant modifications were identified compared with T-30, with an increase in platelet aggregation (collagen:32.6 ± 4.8 vs. 21.6 ± 4.9%; ADP: 35.5 ± 2.0 vs. 24.5 ± 3.1%; A23187: 30 ± 4.7 vs. 23.8 ± 4%) and a shorter closure time of C-ADP cartridges (75.6 ± 4.4 vs. 87.7 ± 3.4 s) that tended to return to the baseline value at T90. NOx concentrations in plasma significantly increased after 30 days of the training program compared with the baseline. The first long-term training period seems to induce platelet hyperactivity after 30 days in never-trained Thoroughbreds. Regular physical training reduces the negative effects of acute efforts on platelet activation.